Infliximab therapy reverses the increase of allograft inflammatory factor-1 in serum and colonic mucosa of rats with inflammatory bowel disease. (17th February 2017) - Román, Irene D.; Cano-Martínez, David; Lobo, María Val T.; Fernández-Moreno, María Dolores; Hernández-Breijo, Borja; Sacristán, Silvia; Sanmartín-Salinas, Patricia; Monserrat, Jorge; Gisbert, Javier P.; Guijarro, Luis G.
Abstract: Objective: Our purpose was to study the molecular basis of infliximab (IFX) effect on colon mucosa in a colitis model and to identify new biomarkers of mucosal healing. Methods: Healthy rats and rats which were subjected to experimental colitis induced by dextran sulfate sodium, with or without IFX treatment (in the short- and long-term), were studied along with forty-seven IBD patients. Colon mucosal integrity by periodic acid Schiff (PAS) staining, intestinal damage by immunohistochemistry (proliferating cell nuclear antigen, β-catenin, E-cadherin, phosphotyrosine, p-p38, allograft inflammatory factor-1 (AIF-1) and colonic mucosal apoptosis by TUNEL staining were evaluated in rats while serum and colon AIF-1 levels were determined in IBD patients. Results: In rats with colitis, IFX reestablished the epithelial barrier integrity, recovered mucus production and decreased colon inflammation, as verified by reduced serum and colon AIF-1 levels; colon and serum AIF-1 levels were also lower in inactive IBD patients compare to active ones. P38 activation after IFX treatment tended to induce differentiation/proliferation of epithelial cells along the colonic crypt-villous axis. Conclusions: These findings support AIF-1 as a new biomarker of mucosal healing in experimental colitis and suggest that p38 activation is involved in the mucosal healing intracellular mechanism induced by IFX treatment.